Isometric and dynamic strength and neuromuscular attributes as predictors of vertical jump performance in 11- to 13-year-old male athletes - McKinlay, B. J.; Wallace, P. J.; Dotan, R.; Long, D.; Tokuno, C.; Gabriel, D. A.; Falk, B. (Applied Physiology, Nutrition, and Metabolism, 2017)
In explosive contractions, neural activation is a major factor in determining the rate of torque development, while the latter is an important determinant of jump performance. However, the contribution of neuromuscular activation and rate of torque development to jump performance in children and youth is unclear. The purpose of this study was to examine the relationships between the rate of neuromuscular activation, peak torque, rate of torque development, and jump performance in young male athletes. Forty-one 12.5 ± 0.5-year-old male soccer players completed explosive, unilateral isometric and dynamic (240°/s) knee extensions (Biodex System III), as well as countermovement-, squat-, and drop-jumps. Peak torque (pT), peak rate of torque development (pRTD), and rate of vastus lateralis activation (Q30) during the isometric and dynamic contractions were examined in relation to attained jump heights. Isometric pT and pRTD were strongly correlated (r = 0.71) but not related to jump performance. Dynamic pT and pRTD, normalized to body mass, were significantly related to jump height in all 3 jumps (r = 0.38-0.66, p < 0.05). Dynamic normalized, but not absolute pRTD, was significantly related to Q30 (r = 0.35, p < 0.05). In young soccer players, neuromuscular activation and rate of torque development in dynamic contractions are related to jump performance, while isometric contractions are not. These findings have implications in the choice of training and assessment methods for young athletes.